First evidence of TRPV5 and TRPV6 channels in human parathyroid glands: possible involvement in neoplastic transformation. Issue 10 (28th August 2014) - Giusti, Laura; Cetani, Filomena; Da Valle, Ylenia; Pardi, Elena; Ciregia, Federica; Donadio, Elena; Gargini, Claudia; Piano, Ilaria; Borsari, Simona; Jaber, Ali; Caputo, Antonella; Basolo, Fulvio; et al.
Abstract The parathyroid glands play an overall regulatory role in the systemic calcium (Ca2+) homeostasis. The purpose of the present study was to demonstrate the presence of the Ca2+ channels transient receptor potential vanilloid (TRPV) 5 and TRPV6 in human parathyroid glands. Semi‐quantitative and quantitative PCR was carried out to evaluate the presence of TRPV5 and TRPV6 mRNAs in sporadic parathyroid adenomas and normal parathyroid glands. Western blot and immunocytochemical assays were used to assess protein expression, cellular localization and time expression in primary cultures from human parathyroid adenoma. TRPV5 and TRPV6 transcripts were then identified both in normal and pathological tissues. Predominant immunoreactive bands were detected at 75–80 kD for both vanilloid channels. These channels co‐localized with the calcium‐sensing receptor (CASR) on the membrane surface, but immunoreactivity was also detected in the cytosol and around the nuclei. Our data showed that western blotting recorded an increase of protein expression of both channels in adenoma samples compared with normal glands suggesting a potential relation with the cell calcium signalling pathway and the pathological processes of these glands.